LRRC25 Functions as an Inhibitor of NF-κB Signaling Pathway by Promoting p65/RelA for Autophagic Degradation. Issue 1 (December 2017) - Feng, Yanchun; Duan, Tianhao; Du, Yang; Jin, Shouheng; Wang, Mingjun; Cui, Jun; Wang, Rong-Fu
Abstract Nuclear factor κB (NF-κB) is a family of critical transcription factors that play a critical role in innate immune responses and inflammation, yet the molecular mechanisms responsible for its tight regulation is not fully understood. In this study, we identified LRRC25, a member of leucine-rich repeat (LRR)-containing protein family, as a negative regulator in the NF-κB signaling pathway. Ectopic expression of LRRC25 impaired NF-κB activation, whereas knockout ofLRRC25 potentiated NF-κB activation and enhanced the production of inflammatory cytokines. Further study demonstrated that the LRR domain of LRRC25 interacted with the Rel Homology domain (RHD) of p65/RelA and promotes the degradation of p65/RelA. Furthermore, LRRC25 enhanced the interaction between p65/RelA and cargo receptor p62, thus facilitating the degradation of p65/RelA through autophagy pathway. Our study has not only identified LRRC25 as a novel inhibitor of NF-κB signaling pathway, but also uncovers a new mechanism of crosstalk between NF-κB signaling and autophagy pathways.